Prezentace GIS pro výuku v terénu - Ráczová, Gabriela (Vysoké učení technické v Brně. Fakulta stavební, 2015)
Náplní této diplomové práce je vytvoření prezentace geografického informačního systému (GIS) lokality Jedovnice. Prezentace GIS Jedovnice bude sloužit pro potřeby výuky v terénu druhého a třetího ročníku oboru Geodézie a kartografie Fakulty stavební VUT v Brně. Zpracování dat je provedeno v programu Marushka Design od firmy Geovap. Správa databázových entit je zpracována v programu SQLite Expert Personal. Prezentace GIS obsahuje bodové pole v dané lokalitě a zadání úloh pro studenty. Navržený systém umožňuje editaci a správu stávajících dat.

The aim of this diploma thesis is to create Geographic Information System (GIS) presentation of Jedovnice location. Created GIS presentation serve as a teaching tool for 2nd and 3rd year of Geodesy and Cartography field, Faculty of civil engineering, University of technology in Brno. Data processing was performed using Marushka Design program of Geovap group. Database entities management was processed in the SQLite Personal program. GIS presentation includes geodetic point field in specified location and tasks assignment for students. Designed system allows editing and managing of data already existed.
Presentation of GIS for Field Training
Keywords: Geografický informační systém (GIS); Marushka Design; SQL; databázové systémy; SQLite Expert Personal; výuka v terénu.; Geographic information system (GIS); Marushka Design; SQL; database system; SQLite Expert Personal; field training.